Sexo, abominação e morte no código de santidade: uma análise crítica da homossexualidade em Levítico 20,13 - Franco, Jose Frederico Sardinha (2017)
The present research aims to understand the male homoerotic practice existing in Leviticus 20:13 during of the Babylonian post-exile. Our initial proposal is based to build understanding through the analysis of the words sex, abomination, death, having the code of holiness (Lv 17-26) in this literary context. In this way, we will use as research methodology, the bibliographic research, developed based on already published books and materials. The Bíblia hebraica Stuttgartensia (1997) will contribute in the translation and analysis of Sacred texts. In addition, we will use the portughese versions of the the Jerusalem Bible (1991) and Almeida Revista e Corrigida (1995), which will help us collect and record data pertinent to the clipping being searched. We have recourse to the historical-critical method that will help us in the textual analysis of all Levitical literature. We will use Leviticus verse 18:23 in the data analysis, due to its similarity to the clipping to be researched, which will be of great value in the exegetical construction of the text. The use of the conflictual method in the analysis in Leviticus 20:13 will make the hermeneutics of the text have a new perspective on the understanding of common sense. The discourse of homosexuality inserted in the Hebrew Bible must be analyzed from temporal perspectives, since it is an old writing from 538 BC, so our effort is to be able to contribute through a sociocultural translation, of the presented clipping in Leviticus 20:13.